Tapping migration wealth to fund development - Jocelyne Sambira (Africa Renewal, 2013)
In a small and stuffy room in midtown Manhattan, some people are filling in forms while others wait patiently in line to submit them. It is spring in New York City but the sweltering heat and the poor ventilation is reminiscent of summer. The teller shielded by a glass window barks orders through a round hole. With one hand on his suitcase, Omar tugs at his collar to loosen the red and blue striped tie around his neck. Pearls of sweat are visible on his forehead. “I am sending money to a person,” he speaks deliberately. Seemingly satisfied with his answer, the teller continues to punch her keyboard and shouts the next question, “How much?” He knows the drill. And like most migrant workers in the city, the trek to this hole in the wall is part of his routine on pay days.